Evaluation of a peer education program on student leaders' energy balance-related behaviors - B. C. Foley; V. A. Shrewsbury; L. L. Hardy; V. M. Flood; K. Byth; S. Shah (BMC, 2017)
Abstract Background Few studies have reported energy balance-related behavior (EBRB) change for peer leaders delivering health promotion programs to younger students in secondary schools. Our study assessed the impact of the Students As LifeStyle Activists (SALSA) program on SALSA peer leaders' EBRBs, and their intentions regarding these behaviors. Methods We used a pre-post study design to assess changes in EBRBs and intentions of Year 10 secondary school students (15-16 year olds) who volunteered to be peer leaders to deliver the SALSA program to Year 8 students (13-14 year olds). This research is part of a larger study conducted during 2014 and 2015 in 23 secondary schools in Sydney, Australia. We used an online questionnaire before and after program participation to assess Year 10 peer leaders' fruit and vegetable intake, daily breakfast eating, sugar sweetened beverage (SSB) intake, moderate-to-vigorous physical activity (MVPA) participation and school-day recreational screen time behaviors and intentions regarding these EBRBs. Generalized estimating equations with a robust variance structure and exchangeable correlation structure were used to estimate the individual-level summary statistics and their 95% CIs, adjusted for clustering. We further assessed the effect of covariates on EBRB changes. Results There were significant increases in the proportion of Year 10 peer leaders (n = 415) who reported eating ≥2 serves fruit/day fruit from 54 to 63% (P < 0.01); eating ≥5 serves vegetables/day from 8 to 12% (P < 0.01); and drinking <1 cup/day of SSBs from 56 to 62% (P < 0.01). Change in ≥60 min MVPA participation/day depended on gender (P < 0.01): Boys increased 14% while girls decreased −2%. Changes in eating breakfast daily also depended on gender (P < 0.004): Boys increased 13% while girls decreased −0.4%. The change in peer leaders recreational screen time differed by socio-economic status (P < 0.05): above average communities decreased by −2.9% while below average communities increased 6.0%. Significant shifts were seen in peer leaders' intentions, except MVPA which remained stable. Conclusions The SALSA program had a positive impact on peer leaders' EBRBs, with gender and socio-economic status moderating some outcomes. Trial registration ACTRN12617000712303 retrospectively registered.